A Novel Dynamical Regulation of mRNA Distribution by Cross-Talking Pathways - Qiwen Sun; Zhaohang Cai; Chunjuan Zhu (Mathematics, 2022)
In this paper, we use a similar approach to the one proposed by Chen and Jiao to calculate the mathematical formulas of the generating function <semantics>V(z,t)</semantics> and the mass function <semantics>Pm(t)</semantics> of a cross-talking pathways model in large parameter regions. Together with kinetic rates from yeast and mouse genes, our numerical examples reveal novel bimodal mRNA distributions for intermediate times, whereby the mode of distribution <semantics>Pm(t)</semantics> displays unimodality with the peak at <semantics>m=0</semantics> for initial and long times, which has not been obtained in previous works. Such regulation of mRNA distribution exactly matches the transcriptional dynamics for the osmosensitive genes in Saccharomyces cerevisiae, which has not been generated by those models with one single pathway or feedback loops. This paper may provide us with a novel observation on transcriptional distribution dynamics regulated by multiple signaling pathways in response to environmental changes and genetic perturbations.